Performance Analysis of anEnhanced AODV Routing Protocol (International Journal of Engineering and Computer Science, 2017)
ThisPaper has modified AODV protocol, designed to improve the performance of Mobile Ad Hoc networks. This paper describes the characteristics, working and deficiency ofAODV routing protocols, and modified AODV routing protocol (MAODV). Finally, using NS2 simulation, results compared to the AODV routing protocol, MAODV routingprotocol in terms of packet delivery ratio, end to end delay, Routing-load and Throughput. Experimental result shows that MAODV routing protocol is more advantages than the AODVrouting protocol.